Mobile Image Interpretation: Diagnostic Performance of CT Exams Displayed on a Tablet Computer in Detecting Abdominopelvic Hemorrhage. - Schlechtweg, Philipp; Kammerer, Ferdinand; Seuss, Hannes; Uder, Michael; Hammon, Matthias (Journal of Digital Imaging, 2016)
To investigate whether abdominopelvic hemorrhage shown on computed tomography (CT) images can be diagnosed with the same accuracy on a tablet computer as on a dedicated reading display. One hundred patients with a clinical suspicion of abdominopelvic hemorrhage that underwent biphasic CT imaging were retrospectively read by two readers on a dedicated reading display (reference standard) and on a tablet computer (iPad Air). Reading was performed in a dedicated reading room with ambient light conditions. Image evaluation included signs of an active hemorrhage (extravasation of contrast media) and different signs indicating a condition after abdominopelvic hemorrhage (hematoma, intestinal clots, vessel stump, free abdominopelvic fluid with a mean Hounsfield unit value >20, and asymmetric muscle volume indicating intramuscular hemorrhage). Sensitivity, specificity, and positive and negative predictive values (PPV/NPV) were calculated for the tablet-based reading. Active abdominopelvic hemorrhage ( n = 72) was diagnosed with the tablet computer with a sensitivity of 0.96, a specificity of 0.93, a PPV of 0.97, and an NPV of 0.90. The results for the detection of the signs indicating a condition after abdominopelvic hemorrhage range from 0.83 to 1.00 in the case of sensitivity, from 0.95 to 1.00 in the case of specificity, from 0.94 to 1.00 in the case of the PPV, and from 0.96 to 1.00 in the case of the NPV. Abdominopelvic hemorrhage shown on CT images can be diagnosed on a tablet computer with a high diagnostic accuracy allowing mobile on-call diagnoses. This may be helpful because an early and reliable diagnosis at any time is crucial for an adequate treatment strategy.